2004
DOI: 10.1002/app.20215
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen permeation resistance of polyethylene, polyethylene/ethylene vinyl alcohol copolymer, polyethylene/modified ethylene vinyl alcohol copolymer, and polyethylene/modified polyamide–ethylene vinyl alcohol copolymer bottles

Abstract: ABSTRACT:The oxygen permeation resistance of polyethylene (PE), polyethylene/ethylene vinyl alcohol copolymer (PE/EVOH), polyethylene/modified ethylene vinyl alcohol copolymer (PE/MEVOH), and polyethylene/modified polyamide-ethylene vinyl alcohol copolymer (PE/MPAEVOH) bottles was investigated. The oxygen permeation resistance improved significantly after the blending of ethylene vinyl alcohol copolymer (EVOH) barrier resins in PE matrices during blow molding; less demarcated EVOH laminas were found on the fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…6 There have been numerous investigations focused on PE/PA or modified PA, PE/poly(vinyl alcohol), and PE/poly(ethylene-co-vinyl alcohol) multilamellar blending systems. [7][8][9] These heterogeneous multilamellar blends exhibit significantly higher permeation barrier properties than those of the conventional homogeneous blends associated with uniformly dispersed PA within the PE matrix. The laminar platelets are formed by melt process of PE, PA, and the other additives in a specially designed blend-blowmolding machine.…”
Section: Introductionmentioning
confidence: 96%
“…6 There have been numerous investigations focused on PE/PA or modified PA, PE/poly(vinyl alcohol), and PE/poly(ethylene-co-vinyl alcohol) multilamellar blending systems. [7][8][9] These heterogeneous multilamellar blends exhibit significantly higher permeation barrier properties than those of the conventional homogeneous blends associated with uniformly dispersed PA within the PE matrix. The laminar platelets are formed by melt process of PE, PA, and the other additives in a specially designed blend-blowmolding machine.…”
Section: Introductionmentioning
confidence: 96%
“…It exhibited improved barrier properties by 10 orders of magnitude. Yeh and coworkers reported that high‐density polyethylene (HDPE) composites containing 10 wt % modified polyamide (MPA) or MPA–EVOH in blown bottles with a laminar structure showed a higher oxygen barrier than pure HDPE at 40°C. However, the formation of stable two‐dimensional sheets in polymer blends is closely related to several basic parameters, including the composition, viscosity ratio, interfacial tension, and processing conditions, which are hard to control in practical processing .…”
Section: Introductionmentioning
confidence: 99%
“…In order to address these shortcomings, a great deal of research has focused on improving the oxygen barrier properties of polymers. Some approaches that have been followed are: blending or laminating high barrier polymers with low barrier polymers [1][2][3][4][5][6]; forming inorganic-organic hybrids, i.e., crosslinking an inorganic material into an organic material (e.g., a polymer) [7][8][9][10]; chemical vapor deposition, where an inorganic carbon or silicon oxide-based coating is deposited onto a plastic substrate [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%